Peningkatan Kemampuan Menulis Cerpen dengan Model Pembelajaran Assisted Learning pada Siswa Kelas IX SMP Jaya Negara Makassar - Inda, Reliana; Tenriana, Nuzul; Iriany, Rosary; Muhdar, Andi; Imran, Imran (AIJER: Algazali International Journal Of Educational Research, 2024)
Abstract: This study aims to determine the application of the Assisted Learning model in improvingshort story writing skills in class IX SMP Jaya Negara Makassar. The type of research used usedclassroom action research (PTK). This research design uses the Kurt Lewin model which includesplanning, action implementation, observation, and reflection. The population of this study were allninth-grade students of SMP Jaya Negara Makassar as many as 21 students. Collection techniques werecarried out by observation, tests, and observation of teacher and student activities. The data collectedwere then analyzed descriptively based on the assessment criteria for understanding short story textwriting in the form of written tests. The results showed that the application of the assisted learningmodel was able to improve the ability to write short stories in class IX SMP Jaya Negara Makassar. Theresults obtained based on the results of cycle II who obtained the KKM score> 75 increased to 18students or (85.7%).